2019
DOI: 10.1039/c9ta05446d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh energy storage and electrocaloric performance achieved in SrTiO3 amorphous thin films via polar cluster engineering

Abstract: High energy storage density and a reversible electrocaloric effect are simultaneously achieved in Sr0.995(Na0.5Bi0.5)0.005(Ti0.99Mn0.01)O3 amorphous thin films via polar cluster engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…In addition, excellent energy storage performance was demonstrated by constructing the PbZr 0.52 Ti 0.48 O 3 /Al 2 O 3 /PbZr 0.52 Ti 0.48 O 3 opposite double-heterojunction due to the ultrahigh E BDS and the high linearity of hysteresis loops caused by a nanosized-grain structure . This research group also reported an approach for achieving high energy storage performance in Sr 0.995 (Na 0.5 Bi 0.5 ) 0.005 ­(Ti 0.99 Mn 0.01 )­O 3 amorphous thin films by embedding crystalline polar clusters in the thin films . These amorphous thin films demonstrated good insulation, resulting in improved E BDS ; this study also confirmed that anisotropic polar nanometer-scale regions could be freely switched with the electric field, thereby leading to large polarization in the thin films.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…In addition, excellent energy storage performance was demonstrated by constructing the PbZr 0.52 Ti 0.48 O 3 /Al 2 O 3 /PbZr 0.52 Ti 0.48 O 3 opposite double-heterojunction due to the ultrahigh E BDS and the high linearity of hysteresis loops caused by a nanosized-grain structure . This research group also reported an approach for achieving high energy storage performance in Sr 0.995 (Na 0.5 Bi 0.5 ) 0.005 ­(Ti 0.99 Mn 0.01 )­O 3 amorphous thin films by embedding crystalline polar clusters in the thin films . These amorphous thin films demonstrated good insulation, resulting in improved E BDS ; this study also confirmed that anisotropic polar nanometer-scale regions could be freely switched with the electric field, thereby leading to large polarization in the thin films.…”
supporting
confidence: 63%
“…There are a certain amount of amorphous phases in the films annealed at 525 °C, which affect the polarization characteristics of the films, thus reducing the maximum polarization of the films. Even if the long-range disordered amorphous phase has weak dielectric properties due to the existence of some nanoclusters, the presence of an amorphous nature in the PCZ film will also affect the polarization properties. In addition, the effect of testing frequency on the polarization behaviors of these films was also investigated (Figure S6), and the results show that the maximum polarization and remanent polarization increased slightly with the decrease of frequency due to the existence of space charge polarization at low frequency …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under an electric field of 1982 kV/cm, www.springer.com/journal/40145 (Sr 0.85 Bi 0.1 )Ti 0.99 Mn 0.01 O 3 possess a W rec of 24.4 J/cm 3 accompanied by the largest ΔP (P max -P r = 34.3 μC/cm 2 ). Actually, the introduction of other Bi-contained compounds such as Bi 0.5 Na 0.5 TiO 3 (BNT) [53], BiFeO 3 (BF) [54] has a similar effect to strengthen relaxor characteristics. For example, Pan et al [54] deposited 5 mol% Mn-doped 0.6SrTiO 3 -0.4BiFeO 3 (0.6ST-0.4BF) thin film on Nb-doped SrTiO 3 single crystal substrate using pulsed laser deposition (PLD), and acquired that W rec and  were 51 J/cm 3 and 64%, respectively.…”
Section: Srtio 3 Based Ceramicsmentioning
confidence: 99%
“…Because the BDS value is one of the most key parameters that determine W , it is necessary to obtain the BDS. The Weibull distributions of BDS for all thin films are exhibited in Figure a. As shown in Figure a, the BDS values are calculated to be 4910, 4910, 4910, and 3970 kV cm –1 for Sr 1– x (Na 0.5 Bi 0.5 ) x Ti 0.99 Mn 0.01 O 3 ( x = 0, 0.005, 0.01, and 0.02) thin films, respectively.…”
mentioning
confidence: 95%